2020
DOI: 10.1016/j.heliyon.2020.e05557
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice among healthcare workers towards COVID-19 outbreak in Nigeria

Abstract: Background: Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection is a global pandemic. Healthcare workers' (HCWs) role in patient management is predisposing and can serve as means of hospitals and community transmission. This study evaluated HCWs' knowledge, attitude, and practice towards COVID-19 in Nigeria. Methods: we carried out a cross-sectional survey among HCWs during the COVID-19 outbreak in Nigeria from March to June 2020. The study assessed 346 HCWs for Knowledge, attitude, and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
72
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 29 publications
22
72
6
2
Order By: Relevance
“…These noted knowledge gaps arose primarily because medical and agricultural majors’ students might have had biological sciences knowledge which is linked to infectious and virus diseases prior to the pandemic, as it might also be in their curriculum of study and is related to their professions which would have positively given them an added advantage of having good knowledge. The general findings of good knowledge on COVID-19 of this study are in agreement with other results that were conducted on similar topics on COVID-19 in other countries like China, India, Bangladesh, Cameroon, Nigeria, and Turkey 6 , 21 , 22 , 31 , 32 , 36 , 37 recently. Furthermore, on knowledge gaps, the study is in conformity with results in other areas where pandemics like Cholera, Ebola, Avian Influenza (H5N1), N1H1 Flu Virus, and COVID-19 knowledge were researched like Thailand, Ecuador, Ethiopia, and Nigeria where they also found that there were knowledge gaps among people depending on social demographic factors like academic background, sex, and age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These noted knowledge gaps arose primarily because medical and agricultural majors’ students might have had biological sciences knowledge which is linked to infectious and virus diseases prior to the pandemic, as it might also be in their curriculum of study and is related to their professions which would have positively given them an added advantage of having good knowledge. The general findings of good knowledge on COVID-19 of this study are in agreement with other results that were conducted on similar topics on COVID-19 in other countries like China, India, Bangladesh, Cameroon, Nigeria, and Turkey 6 , 21 , 22 , 31 , 32 , 36 , 37 recently. Furthermore, on knowledge gaps, the study is in conformity with results in other areas where pandemics like Cholera, Ebola, Avian Influenza (H5N1), N1H1 Flu Virus, and COVID-19 knowledge were researched like Thailand, Ecuador, Ethiopia, and Nigeria where they also found that there were knowledge gaps among people depending on social demographic factors like academic background, sex, and age.…”
Section: Discussionsupporting
confidence: 93%
“…39,40 However, the results were in agreement with recent studies done Nigeria, China, and India where they also found that many people had a positive attitude towards COVID-19 and Cholera believed that they would fight and win anytime. 6,21,36 With regard to their views on safety, international students confidently indicated that they felt safe being in China despite the outbreak of COVID-19, which was also attributed to the measures that the authorities implemented to make sure foreigners living in China, including students, were guaranteed of their safety. 24 It therefore indicated that international students saw COVID-19 as a global pandemic infectious disease that was normal like any other pandemics which was supposed to be taken with all human collaboration without looking at where it came from or associating it with a certain group of people.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest age group documented in the present study was 29-38year olds with a mean age of 30.78 ± 4.71years. This was comparable with similar age groups of 30-39years, 31-35years, 30-34years, 25-35years and 18-39years reported by Ejeh et al, [14] Anikwe et al, [15] Omozuwa et al, [16] Edet et al [17] and Reuben et al [18] respectively. This however contrast the lower age groups of 12-24years, 20-29years, 20-29years, 21-30years and < 25years documented by Sayedahmed et al, [19] Nicholas et al, [20] Hoque et al, [21] Ogbole et al [22] and Kamal et al [23] respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Each person’s compliance with preventive guidelines is mostly affected by their KAP toward COVID-19 under KAP theory [ 11 ]. In previous studies about infectious diseases, including Middle East respiratory syndrome (MERS) [ 12 ] and severe acute respiratory syndrome (SARS) [ 13 ], the knowledge and attitudes were found to be correlating variables with preventive practice. A few KAP studies on COVID-19 reported similar findings, and most of them were conducted on native college or university students majoring in nursing or medicine [ 14 , 15 , 16 ], which may be not be generalizable to international students.…”
Section: Introductionmentioning
confidence: 99%